A Survey on SQL injection: vulnerabilities, attacks, and prevention techniques - Kindy, Diallo Abdoulaye; Pathan, Al-Sakib Khan (2011)
In this paper, we present a detailed review on various types of SQL injection attacks, vulnerabilities, and prevention techniques. Alongside presenting our findings from the survey, we also note down future expectations and possible development of countermeasures against SQL injection attacks.